Apoptosis during the seasonal spermatogenic cycle of Rana catesbeiana - Sasso-Cerri, E. (2006)
In the bullfrog Rana catesbeiana, testicular weight is constant throughout the year, but the volume densities of germinative and interstitial compartments undergo inverse changes from winter (non-breeding) to summer (breeding). The occurrence of apoptosis in the seminiferous lobules of bullfrogs was investigated in these two periods using sections stained with haematoxylin and eosin (H&E), the TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end labelling) method and transmission electron microscopy. TUNEL-positive cells were observed in the seminiferous lobules, and ultrastructural morphological details confirmed the occurrence of cell death by apoptosis. In summer, the occurrence of several spermatogenic processes (in addition to spermiogenesis and spermiation), and then the overconsumption of Sertoli cell-derived pro-survival factors, could be responsible for the increased density of apoptotic cells. Alternatively, the low apoptotic frequency in winter could be related to the constant homeostasis in the germinative compartment given that most lobules are filled with primary spermatocytes. As volume densities of interstitial and germinative compartments undergo inverse seasonal variations through the year, the incidence of apoptosis (in summer) could play a part in controlling the spermatogenic process, maintaining the lobular size when interstitial tissue is maximally developed. In winter, the low apoptotic cell density leads to spermatogenic recrudescence and, thereby, the production of an adequate quantity of spermatozoa for the next breeding period. Thus, apoptosis may participate not only in the maintenance of spermatogenic homeostasis, but also in the cyclical control of the different spermatogenic processes according to seasonal changes of the testicular compartments as a whole.